Association of smoking status and smoking intensity with general and abdominal obesity in a sample of middle-aged men - A. A. Alexandrov; V. B. Rozanov; V. A. Dadaeva; M. B. Kotova; E. I. Ivanova; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2020)
Aim. To assess the association of smoking status and smoking intensity with general and abdominal obesity in a sample of middle-a ged men.Material and methods. This study was conducted as a part of the 32-year prospective cohort observation of males from childhood (11-12 years of age). The study included 301 (30,0%) representatives of the initial population sample aged 41-44 years. Age, anthropometric parameters, relationship of smoking status and smoking intensity with general (overweight/obesity) and abdominal obesity were analyzed.Results. Overweight/obesity were more common in former smokers (78,1%) compared with non-smokers (58,7%; p<0,01). Abdominal obesity, estimated by the waist circumference (WC), was detected more often among former (57,5%) and current smokers (50,7%), and abdominal obesity, estimated by the waist-to-hip ratio, was more common among current smokers, compared with non-smokers (37,0%; p<0,01, p<0,05 and p<0,05 respectively). A direct linear relationship was found between the intensity of current smoking and indicators of abdominal obesity in terms of waist-to-hip ratio (P for trend=0,004) and a direct linear relationship between intensity of former smoking and general obesity estimated by BMI (P for trend = 0,001), and abdominal obesity estimated by waist-tohip ratio (P for trend=0,004). The probability of developing abdominal obesity in current smokers with WC≥94,0 cm and with waist-to-hip ratio ≥0,9 was 1,8 and 2 times higher, respectively, than in non-smokers, but lower compared to former smokers. The risk of overweight/obesity and abdominal obesity in former smokers was 2,5 and 2,3 times higher, respectively, than in non-smokers. The 10-year risk of fatal CVD in nonsmokers and former smokers was lower than in current smokers (0,8% and 0,9% vs 1,8%; p<0,001 and p<0,001, respectively).Conclusion. High intensity of smoking among current smokers is associated with a higher probability of developing abdominal obesity, and in former smokers — with a higher probability of developing general and abdominal obesity. Former smokers, compared to current smokers, are at a lower risk of developing fatal cardiovascular diseases. Smoking cessation activities should be aimed at minimizing weight gain after quitting smoking and developing tobacco control programs.